Physiological responses of Eucalyptus spp. hybrids to infection by Ceratocystis fimbriata. Issue 4 (8th February 2017) - Pimenta, L.; Ferreira, M. A.; Ribeiro, P. M.; Zacaroni, L. M.; Mafia, R. G.; Resende, M. L. V.
Summary: In Brazil, the selection and planting of eucalyptus clones resistant to Ceratocystis fimbriata is the pre‐eminent control strategy for the wilt pathogen. However, little is known about host defence responses associated with resistance of eucalyptus to C. fimbriata infection. In this work, enzymatic activity, sugars, lignin, total phenols and phenolic compounds involved in the defence response of eucalyptus clones resistant (RC) and susceptible (SC) to the Ceratocystis wilt were evaluated. Changes were detected in the sugars produced by RC clones, with higher concentrations occurring compared with SC. A similar response occurred with lignin content at 28 days after inoculation (dai) in RC plants. SC plants had an increase in polyphenol oxidase and peroxidase activities at 7 dai. In contrast, RC plants demonstrated high activity of the same enzymes at 2 and 4 dai, decreasing afterwards. There was no difference in phenylalanine ammonia‐lyase activity between resistant and susceptible clones. Hydroxycinnamic acid concentration was higher in RC than in SC; however, there was no difference between RC and SC in flavonoid concentrations. RC had high concentrations catechin, chlorogenic acid and caffeic acid. Histochemical tests demonstrated the presence of phenolic compounds and lignin, at higher intensities, in xylem of RC plants. Inoculation with C . fimbriata induced defence responses in both resistant and susceptible eucalyptus clones, but both the intensity and speed of the responses were higher in RC. Alterations in the concentrations of sugars and lignin, as well as certain enzymes and phenolic compounds, could be used to predict the relative susceptibilities to Ceratocystis wilt of different phenotypes of eucalyptus clones.